FACTORS AFFECTING HIGH SCHOOL AND UNIVERSITY STUDENTS TO SPEEDING - Dewanti Dewanti; Jan Prabowo Harmanto (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2019)
This study aims to find factors influencing students to do speeding in Yogyakarta Special Region. 179 respondents filled in on-line and off-line questionnaires to determine options or probabilities of speeding up on a variety of different road / environmental conditions. Cross tab tests and ordered logistic regression are adopted to analyze influencing factors (both internal and external). 3 of 18 predictor variables do not affect speeding behavior, and those are driving experience, road separator, and speed limit signs. While the age, education, and police presence are negatively correlated with speeding behavior, it means that the older, and the higher a person's education and the presence of police, people tend not to have speeding behavior. The other research result is the level order of the influencing factor of speeding (predictor variables). Penelitian ini bertujuan menemukan faktor – faktor yang mempengaruhi pelajar dan mahasiswa melakukan ‘speeding’ atau ngebut di Daerah Istimewa Yogyakarta. Sebanyak 179 responden mengisi kuesioner on-line maupun off-line untuk mengetahui pilihan-pilihan atau probabilitas melakukan ngebut untuk berbagai kondisi jalan/lingkungan yang berbeda. Uji cross tab dan regresi logistic ordinal digunakan untuk menganalisis factor-faktor (baik internal maupun eksternal) yang berpengaruh. Dari 18 variabel predictor, 3 diantaranya tidak berpengaruh, yaitu: pengalaman berkendara, pemisah jalan dan rambu batas kecepatan. Sementara variable usia, pendidikan dan keberadaan polisi berkorelasi negative terhadap perilaku ngebut, artinya semakin bertambah usia, dan makin tinggi pendidikan seseorang serta adanya polisi mendorong orang untuk tidak ngebut. Dihasilkan juga urutan tingkat pengaruh masing-masing factor (variable predictor)